Love & war : an Alex & Eliza story - De la Cruz, Melissa, 1971- (New York, NY : G.P. Putnam's Sons, 2018)
"As the end of the American Revolution nears, newlyweds Alex and Eliza are faced with new trials and temptations"--
VOYA (Voice of Youth Advocates Magazine)
Booklist
Kirkus Reviews
Keywords: Hamilton, Alexander, -- 1757-1804 -- Juvenile fiction; Hamilton, Elizabeth Schuyler, -- 1757-1854 -- Juvenile fiction; United States -- History -- Revolution, 1775-1783 -- Juvenile fiction